Factors Associated With Early Deaths Following Neonatal Male Circumcision in the United States, 2001 to 2010. (November 2018) - Earp, Brian D.; Allareddy, Veerajalandhar; Allareddy, Veerasathpurush; Rotta, Alexandre T.
We sought to quantify early deaths following neonatal circumcision (same hospital admission) and to identify factors associated with such mortality. We performed a retrospective analysis of all infants who underwent circumcision in an inpatient hospital setting during the first 30 days of life from 2001 to 2010 using the National Inpatient Sample. Over 10 years, 200 early deaths were recorded among 9 833 110 subjects (1 death per 49 166 circumcisions). Note: this figure should not be interpreted as causal but correlational as it may include both undercounting and overcounting of deaths attributable to circumcision. Compared with survivors, subjects who died following newborn circumcision were more likely to have associated comorbid conditions, such as cardiac disease (odds ratio [OR] = 697.8 [378.5-1286.6]; P < .001), coagulopathy (OR = 159.6 [95.6-266.2]; P < .001), fluid and electrolyte disorders (OR = 68.2 [49.1-94.6]; P < .001), or pulmonary circulatory disorders (OR = 169.5 [69.7-412.5]; P < .001). Recognizing these factors could inform clinical and parental decisions, potentially reducing associated risks.